THE REPRESSION OF MARITAL RAPE IN MALAGASY LAW: A TENSION BETWEEN LEGAL RECOGNITION AND SOCIAL DENIAL - Andriamaharitra, Paul Alberti (Indonesian Law Journal, 2025)
Despite the adoption of Law No. 2019-008 of January 16, 2020, which formally criminalizes marital rape in Madagascar, the offense remains socially invisible and judicially neglected. This article explores the contradiction between legal recognition and the persistent lack of enforcement. It investigates how entrenched cultural norms, particularly the presumption of perpetual spousal consent, hinder the acknowledgment and prosecution of marital rape. Relying on a multidisciplinary methodology—legal analysis, sociocultural inquiry, and review of judicial practices—the study identifies systemic obstacles, from patriarchal ideology to institutional inertia. It highlights the gap between the symbolic presence of the norm and its weak application. The article argues for a holistic approach to reform, including the training of legal actors, public awareness on consent within marriage, and the deconstruction of harmful gender norms. By critically analyzing the social and legal reception of this crime, the study contributes to the broader debate on gender-based violence and legal effectiveness in Madagascar.